Administrative Burden at the Regional Secretariat of Semarang Regency, Indonesia - Gunawan, Dedi; Aldafi Prana Tantri (HM Publisher, 2024)
The administrative burden at the Semarang Regency Regional Secretariat office is one of the problems that needs attention, because effective and efficient public services are needed. The duties and functions of the regional secretariat are determined by Regent Regulation (Perbup) number 109 of 2021. Based on this regulation, there are vulnerabilities that will occur in the Semarang Regency Regional Secretariat agency to carry out ineffective and efficient public services. So that in this paper will examine more deeply the administration burden in the Regional Secretariat of Semarang District. The research method is carried out empirically by exploring data in the field and collecting data through interviews with Semarang Regency Regional Secretariat employees. The results of this study indicate the fact that the main problem of administrative burden in the Semarang district secretariat is the low regional budget given and the high responsibility between departments in the regional secretariat, causing employees to be unable to complete the given burden. The solution is done by increasing the regional budget of Semarang Regency and simplifying the bureaucracy in the tasks assigned in Regent regulation number 109 of 2021.